THERAPEUTIC EFFECTS OF FERULA MOSCHATA ROOT ON TESTICULAR CHANGES IN MALE RATS WITH CHRONIC KIDNEY DISEASE - Tilavov Tolibjon Baxtiyor ugli1; Khasanova Dilnoza Akhrorovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Chronic kidney disease (CKD) is a progressive and globally increasing health burden, affecting over 850 million people worldwide and estimated to become the fifth leading cause of death by 2040. In addition to renal insufficiency, CKD is associated with systemic complications, including reproductive dysfunction in males. These complications often manifest as hypogonadism, reduced testosterone secretion, impaired spermatogenesis, and testicular atrophy, leading to infertility